Our students are they healthy? - Mohd Rashid, Muhammad Hakimi; Tin, Myo Han; Aminuddin, Niferiti; Abdul Razak, Tariq (2014)
Background: Cardiovascular disease remains the leading cause of death worldwide. Recent studies showed an alarming trend for cardiovascular risk profile among young adults. Among the many risk factors of cardiovascular disease, cholesterol is considered as the required risk factor. This study is part of a clinical trial approved by IIUM ethical committee. Methodology: A total of 63 male subjects came to join the study. After a briefing session, only 33 subjects agreed to enroll and were screened. Each subject was assessed by a physician. Their weight, height, blood pressure (supine and upright), heart rate, and ECG were taken. Blood samples were withdrawn from antecubital vein for fasting lipid profile. Subjects were asked to fast overnight (10 hours) prior to screening. Result: Their mean (SD) age was 22.9 (2.2) years, their mean (SD) BMI was 22.7 (3.2), their supine systolic (SBP) and diastolic (DBP) blood pressure were 111.9 (9.8)mmHg and 68.0 (6.5)mmHg, their standing SBP and DBP were 117.6 (9.8)mmHg and 74.5 (7.1)mmHg, the total cholesterol was 4.8 (0.7)mmol/L, HDL was 1.3 (0.2)mmol/L, LDL was 3.0 (0.7)mmol/L and triglyceride was 1 (0.7)mmol/L. the total cholesterol level in this study’s participants was significantly higher than in general Malaysian population aged 30-40 (4.8 vs. 4.5)(p<0.05). The proportion of study participants with hypercholesterolemia is 28.1% (26.6% in NHMS 2011). Conclusion: The total cholesterol levels among IIUM students in our study were significantly higher as compared to general Malaysian population aged 30-40 years.